High-quality blasting cotton and preparation method thereof
Patent Information
- Application Number
- CN202311728477.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-15
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2043-12-15
AI Technical Summary
使得产品在溶解、凝胶过程中存在溶解速度慢、凝胶形成慢、形成的凝胶不够稳定等问题
[0023]理论上,物料的颗粒越小,溶解越快,对于细小纤维的物料,常理推断比较大纤维的物料溶解快。但实际上细小纤维的物料,会聚集成团,外部溶解后形成包裹,阻碍进一步溶解;而较大纤维的物料,溶解速度适中,形成包裹的情况较少,反而整体溶解较快。实际生产的物料,既有细小纤维,又有较大纤维(不同大小的纤维混合在一起),细小纤维含量越少,总体溶解越快,粘度增长越快,形成凝胶越好。因此本发明对其生产过程中的进料、煮洗、细断进行了优化,并增加了原材料除尘和细断后水筛、重力沉降去除细小纤维等工艺,从而降低产品中细小纤维数目的含量,极大地改善了爆胶棉在溶剂中的溶解性能及成胶性能。
Abstract
Description
Technical Field
[0001] This invention relates to the field of nitrocellulose manufacturing, and more particularly to a high-quality bursting cotton and its preparation method. Background Technology
[0002] Nitrocellulose, also known as nitrocellulose for blasting explosives, mainly acts as a gel in blasting explosives. After absorbing nitroglycerin, it is mixed with oxidizers, combustibles, additives, etc. to form a plastic body, which is then kneaded into shape. It is widely used in rock blasting and underwater blasting projects.
[0003] Because gelatinous explosives, widely used in industrial blasting, are extremely powerful, the most crucial gelling agent in these explosives, the gelling agent, has extremely strict requirements for its physicochemical properties, especially its viscosity. Considering the waterproof and freeze-resistant properties of gelatinous explosives, the gelling agent must have a very high viscosity. Ordinary gelatinous explosives require the gelling agent with a viscosity of 50 Engel's degree or higher; for non-freezing gelatinous explosives, to prevent the precipitation of crystallized nitroglycerin after freezing, the gelling agent needs an even higher viscosity (above 160 Engel's degree); and in some special industrial applications, even ultra-high viscosity gelling agent (above 1000 Engel's degree) is required.
[0004] Patent CN102219862A describes a method for preparing ultra-high viscosity energetic cellulose nitrate ester (explosive cotton). The explosive cotton prepared by this method contains numerous short, dust-like fine fibers. During the gelation process of the gel explosive, due to the large specific surface area and short length of these fine fibers, they have more thorough contact with the solvent and preferentially dissolve, forming a solution of a certain viscosity. This reduces the fluidity of the solvent. Furthermore, larger fibers are encapsulated by the solution formed by the dissolution of the fine fibers, slowing down the dissolution of the larger fibers, and in some cases, a large amount of the explosive cotton cannot be dissolved. This results in problems such as slow dissolution rate, slow gel formation, and unstable gel during the dissolution and gelation process.
[0005] Therefore, there is an urgent need to develop a type of bursting cotton to solve the above problems. Summary of the Invention
[0006] Based on the shortcomings of the existing technology, the present invention aims to prepare a high-quality bursting cotton, reduce the content of fine fibers in the product, and greatly improve the solubility and gelling properties of the bursting cotton in solvents.
[0007] According to one aspect of the present invention, a method for preparing high-quality bursting cotton includes the following steps:
[0008] S1. Sift the refined cotton through a sieve to remove cotton dust;
[0009] S2. Refined cotton undergoes a nitration reaction in a mixed acid of nitrate and sulfur, followed by filtration and rinsing with tap water to obtain nitrocellulose.
[0010] S3. The nitrocellulose is subjected to acid boiling, water washing, alkali boiling, and fine cutting.
[0011] S4. The material obtained in S3 is subjected to a water sieve;
[0012] S5. The material obtained in S4 is subjected to a sedimentation process to remove fine fibers by stirring, settling, and taking water.
[0013] Furthermore, in step S1, the screen mesh size is 5-20 mesh, the sieving time is more than 10 minutes, and the sieving process disperses the clumps of material; the moisture content of the fine cotton is 5-10%, and the degree of polymerization is more than 2000.
[0014] Further, in step S2, the weight percentage of the nitric acid-sulfur mixture includes: 26.00% to 35.00% nitric acid, 45% to 61% sulfuric acid, and 13.00% to 20.00% water; preferably, the mixed acid components are mainly used to control the nitrogen content.
[0015] Furthermore, in step S2, the nitration reaction time is 30–60 min.
[0016] Further, in step S3, the acid used for acid cooking is calculated as sulfuric acid, with an acidity of 5-7 g / L, an acid cooking temperature of 50-80°C, and an acid cooking time of 2-5 h; the alkalinity used for alkali cooking is calculated as sodium carbonate, with an alkalinity of 0.5-3.0 g / L, an alkalinity of 80-110°C, and an alkalinity cooking time of 1-4 h.
[0017] Furthermore, in step S3, the fineness of the fine-fractionation process is 100-180 ml, and the fine-fractionation time is 50-150 min.
[0018] Furthermore, in step S4, the mesh size of the water sieve is 40 to 120 mesh, and the material is rinsed with tap water during the water sieve process.
[0019] Furthermore, in step S5, the sedimentation process for removing fine fibers involves: first stirring evenly, then performing sedimentation treatment. Utilizing the principle that fine fibers settle slowly, by controlling the sedimentation time, while the fine fibers remain in the upper layer of water before they have completely settled, the upper layer of water and the fine fibers contained therein are extracted.
[0020] Furthermore, the stirring time is more than 10 minutes, the stirring speed is 500 to 3000 r / min, and the settling time is 10 to 30 minutes.
[0021] According to another aspect of the present invention, a high-quality extruded cotton is provided for use in the production of gelatinous explosives for underwater blasting.
[0022] Compared with the prior art, the beneficial effects of the present invention are:
[0023] Theoretically, the smaller the particle size of a material, the faster it dissolves. It's logical to assume that fine fiber materials dissolve faster than larger fiber materials. However, in reality, fine fiber materials tend to clump together, forming encapsulations after dissolution, hindering further dissolution. Larger fiber materials, on the other hand, dissolve at a moderate rate, forming fewer encapsulations and thus dissolving faster overall. In actual production, materials contain both fine and larger fibers (a mixture of fibers of different sizes). The lower the content of fine fibers, the faster the overall dissolution, the faster the viscosity increase, and the better the gel formation. Therefore, this invention optimizes the feeding, washing, and fine cutting processes in its production, and adds processes such as raw material dust removal and water sieving and gravity sedimentation after fine cutting to remove fine fibers. This reduces the number of fine fibers in the product, greatly improving the solubility and gelling properties of the bursting cotton in solvents.
[0024] Compared with the preparation technology of patent CN102219862A, the popping cotton produced by the method of this invention is easier to break into fine pieces. The original process required 150 minutes for the popping cotton after boiling and washing to break into pieces with a fineness of 150ml, while the popping cotton after the current process only requires 80 minutes to break into fine pieces. It also dissolves faster in solvents such as DEP. The original process required more than 3 hours for the popping cotton with a moisture content of 1.2% to completely dissolve, while the popping cotton produced by the current process only takes 1 hour to dissolve. It also gels faster and produces a more stable gel in triacetylglycerol and nitroglycerin. The popping cotton with a moisture content of 3.1% produced by the original process formed a gel in a beaker for 10 minutes, and after being inverted, the gel fell off after 3 minutes. However, the popping cotton produced by the current process can maintain the gel for more than 60 minutes. Detailed Implementation
[0025] To facilitate understanding of the present invention, a more comprehensive description will be provided below. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a thorough and complete understanding of the disclosure of the present invention. Unless otherwise defined, all technical and scientific terms used in this invention pertain to the technical field of the invention.
[0026] The analytical method for the obtained bursting cotton product is as follows;
[0027] Methods for analyzing the quality of bursting cotton gel:
[0028] 1. Experimental preparation
[0029] Laboratory: Turn on the air conditioner in advance and set the temperature (20±1℃). Place a thermometer and hygrometer in the room to monitor the actual temperature. Adjust the air conditioner temperature according to the temperature until the room temperature reaches the required level.
[0030] Samples: Place the samples to be tested and the reagents to be used in the laboratory half an hour in advance to keep them at room temperature.
[0031] 2. Experimental Procedure
[0032] (1) Moisture measurement: Use a rapid moisture analyzer (MB120) to test the moisture content of the pop-up cotton (the moisture content should be between 28-32%).
[0033] (2) Sample weighing: Weigh 89.2g of triacetin (or nitroglycerin) and 7.7g of DBP (dibutyl phthalate) in a 400mL tall beaker and mix them in the beaker; sieve the sample with a 6-mesh standard sieve, retain the sieve material, and then weigh 3.1g of dry amount of the popped cotton sample according to the moisture content.
[0034] (3) Gel preparation: Place the beaker horizontally on the table, hold the beaker steady with one hand, and use a glass rod to quickly stir the popping cotton for 2-3 seconds to evenly disperse it in the gelling agent. After 2, 4, 7, and 10 minutes, invert the beaker and hold it for 5 seconds to check if the mixture falls off.
[0035] (4) Measurement: After 10 minutes, keep the beaker upside down, observe and record the time it takes for the gel to break down and flow / fall off. The time it takes for the gel to break down and flow / fall off is the gel time of the bursting cotton.
[0036] Rotational viscosity analysis method for bursting cotton:
[0037] 1. Experimental preparation
[0038] Laboratory: Turn on the air conditioner in advance, set the temperature, place a thermometer and hygrometer in the room to monitor the actual temperature, and adjust the air conditioner temperature according to the temperature until the room temperature is maintained at 20±1℃.
[0039] Rotational viscometer (Brookfield DV-1): Turn on the power to the viscometer, use the level screw at the bottom of the stand to adjust the viscometer to a horizontal position (observe and confirm that the bubble in the bubble level at the front of the head is in the center area), and then click on the viscometer to automatically zero.
[0040] Samples: Place the samples to be tested and the reagents to be used in the laboratory half an hour in advance to keep them at room temperature.
[0041] 2. Experimental Procedure
[0042] (1) Moisture measurement: Use a rapid moisture analyzer (MB120) to test the moisture content of the pop-up cotton (the moisture content should be between 28-32%).
[0043] (2) Sample weighing: Weigh 80.0g of diethyl phthalate (DEP) in a 100mL tall beaker; sieve the sample with a 6-mesh standard sieve, retain the sieve material, and then weigh the popped cotton sample based on a moisture content of 0.68g dry weight (1.2% moisture content is converted to 30% moisture content).
[0044] (3) Preparation of viscosity solution: Replace the electric stirrer (D2010W) with a special vortex adhesive stirring paddle, place the tall beaker containing DEP under the stirring paddle, and adjust the height of the stirring paddle so that the blades are completely submerged, 10-15mm from the bottom. Turn on the electric stirrer, adjust the speed to 200-400r / min, and after the speed stabilizes, add the weighed popped cotton sample and start timing.
[0045] (4) Rotational Viscosity Measurement: Select a suitable rotor and rotation speed combination (the rotor model must match the model displayed on the operating section). Generally, try different rotors from the highest viscosity 4# to 1#. Note that when inserting the rotor into the solution, the rotor must be immersed in the sample up to the groove mark on the rotor. Press the "Motor On" button to start measuring the viscosity. Before taking the reading, allow a period of time for the reading to stabilize. Note that each time you change the rotor or sample, press the "MOTER ON / OFF / ESCAPE" button to turn off the electrode before operating. Measure and record the solution viscosity value every 10 minutes within 60 minutes.
[0046] The present invention will be further described below through specific embodiments.
[0047] Example 1
[0048] Add 2000g of a nitric acid-sulfur mixture to a 3000ml beaker equipped with a mechanical stirrer. Maintain the temperature at 18℃ for 10 minutes, then start stirring. The mass fractions of the components in the mixture are 27.04% nitric acid, 57.13% sulfuric acid, and 15.84% water. Weigh 50g of M1000 refined cotton (degree of polymerization 2000) dried to 10% moisture content, break it up, and sieve it through a 10-mesh sieve to remove cotton powder for 15 minutes. Add the sieved refined cotton to the mixture. After 40 minutes, filter the mixture and nitrocellulose. Wash the nitrocellulose until it reaches a weakly acidic / neutral pH. Acid-wash the washed nitrocellulose in a beaker containing 2000ml of water, adjusting the acidity to 6g / L. Acid-wash at 70℃ for 3 hours. After acid cooking, wash until weakly acidic / neutral. Then, perform an alkaline wash in a beaker containing 2000ml of water, adjusting the alkalinity to 1.5g / L. Cook at 90℃ for 1.5 hours. Finely break down the nitrocellulose using a Walley pulper at a 3% material concentration for 80 minutes, achieving a fineness of 152ml. Then, sieve the product through a 70-mesh standard sieve. Place the product in 2000ml of water and stir at 1000r / s for 10 minutes. Allow it to settle naturally for 15 minutes, discarding the supernatant. Filter the material through a cloth bag and dehydrate to obtain the bursting cotton product.
[0049] The resulting nitrocellulose (exploding cotton) has a nitrogen content of 194.6 ml / g, a 3% acetone viscosity of 7801 mpa.s, a fine fiber content of 48.1%, and meets the requirements for alcohol-ether solubility, fineness, and stability. It can be used for the production of gelatinous explosives for underwater blasting.
[0050] Dissolution test: In DEP solvent, the viscosity of the 1.2% (moisture content) popping cotton solution reached 3500 mpa.s after 10 minutes and 6000 mpa.s after 60 minutes.
[0051] Gel test: In nitroglycerin and triacetyl ester, 3.1% (dry weight) of the blister cotton gelled in a beaker for 10 minutes and then inverted, maintained stable gel for 90 minutes without falling off.
[0052] Example 2
[0053] Add 2000g of a nitric acid-sulfur mixture to a 3000ml beaker equipped with a mechanical stirrer. Maintain the temperature at 18℃ for 10 minutes, then start stirring. The mass fractions of the components in the mixture are 27.14% nitric acid, 56.75% sulfuric acid, and 16.11% water. Weigh 50g of M1000 refined cotton (degree of polymerization 2500) dried to 5% moisture content, break it up, and sieve it through a 5-mesh sieve to remove cotton powder for 10 minutes. Add the sieved refined cotton to the mixture. After 30 minutes, filter the mixture and nitrocellulose. Wash the nitrocellulose until it reaches a weakly acidic / neutral pH. Acid-wash the washed nitrocellulose in a beaker containing 2000ml of water, adjusting the acidity to 5g / L. Acid-wash at 50℃ for 5 hours. After acid boiling, wash until weakly acidic / neutral. Then, perform an alkaline wash in a beaker containing 2000ml of water, adjusting the alkalinity to 0.5g / L. Boil at 80℃ for 4 hours. Finely break down the nitrocellulose using a Walley pulper at a 3% material concentration for 50 minutes, achieving a fineness of 100ml. Then, sieve the product through a 40-mesh standard sieve. Place the product in 2000ml of water and stir at 3000r / s for 15 minutes. Allow it to settle naturally for 10 minutes, discarding the supernatant. Filter the material through a cloth bag and dehydrate to obtain the bursting cotton product.
[0054] The resulting nitrocellulose (exploding cotton) has a nitrogen content of 194.1 ml / g, a 3% acetone viscosity of 6301 mpa.s, a fine fiber content of 45.1%, and meets the requirements for alcohol-ether solubility, fineness, and stability. It can be used in the production of gelatinous explosives for underwater blasting.
[0055] Dissolution test: In DEP solvent, the viscosity of the 1.2% (moisture content) popping cotton solution reached 4000 mpa.s after 10 minutes and 6200 mpa.s after 60 minutes.
[0056] Gel test: In nitroglycerin and triacetyl ester, 3.1% (dry weight) of the blister pack gelled in a beaker for 10 minutes and then inverted, maintained stable gelation for 120 minutes without falling off.
[0057] Example 3
[0058] Add 2000g of a nitric acid-sulfur mixture to a 3000ml beaker equipped with a mechanical stirrer. Maintain the temperature at 20℃ for 10 minutes, then start stirring. The mass fractions of the components in the mixture are 28.54% nitric acid, 55.88% sulfuric acid, and 15.58% water. Weigh 50g of M1000 refined cotton (degree of polymerization 3000) dried to 8% moisture content, break it up, and sieve it through a 20-mesh sieve to remove cotton powder. Sieve for 20 minutes, then add the sieved refined cotton to the mixture. After 60 minutes, filter the mixture and nitrocellulose. Wash the nitrocellulose until it reaches a weakly acidic / neutral pH. Acid-wash the washed nitrocellulose in a beaker containing 2000ml of water, adjusting the acidity to 7g / L. Acid-wash at 80℃ for 2 hours. After acid cooking, wash until weakly acidic / neutral. Then, perform an alkaline wash in a beaker containing 2000ml of water, adjusting the alkalinity to 3.0g / L. Cook at 110℃ for 1 hour. Finely break down the nitrocellulose using a Walley pulper at a 3% material concentration for 150 minutes, achieving a fineness of 180ml. Then, sieve the product through a 120-mesh standard sieve. Place the product in 2000ml of water and stir at 500r / s for 20 minutes. Allow it to settle naturally for 30 minutes. Discard the supernatant water. Filter the material through a cloth bag and dehydrate to obtain the bursting cotton product.
[0059] The resulting nitrocellulose (exploding cotton) has a nitrogen content of 197.3 ml / g, a 3% acetone viscosity of 5100 mpa.s, a fine fiber content of 50.7%, and meets the requirements for alcohol-ether solubility, fineness, and stability. It can be used in the production of gelatinous explosives for underwater blasting.
[0060] Dissolution test: In DEP solvent, the viscosity of the 1.2% (moisture content) popping cotton solution reached 3200 mpa.s after 10 minutes and 5500 mpa.s after 60 minutes.
[0061] Gel test: In nitroglycerin and triacetyl ester, 3.1% (dry weight) of the blister cotton gelled in a beaker for 10 minutes and then inverted, maintained stable gel for 80 minutes without falling off.
[0062] To further illustrate the key aspects of this patent, comparative examples are provided.
[0063] Comparative Example 1
[0064] Add 2000g of a nitric acid-sulfur mixture to a 3000ml beaker equipped with a mechanical stirrer. Maintain the temperature at 18℃ for 10 minutes, then start stirring. The mass fractions of the components in the mixture are 27.26% nitric acid, 56.79% sulfuric acid, and 15.95% water. Weigh 50g of M1000 refined cotton dried to below 10% moisture content, loosen it, and add it to the mixture. After 40 minutes, filter the mixture and the nitric acid-cotton mixture. Wash the nitric acid-cotton mixture until it is weakly acidic / neutral. Acid-wash the washed nitric acid-cotton mixture in a beaker containing 2000ml of water, adjusting the acidity to 2g / L, and boiling at 80℃ for 2 hours. After acid boiling, wash until it is weakly acidic / neutral. Alkali-wash the washed nitric acid-cotton mixture in a beaker containing 2000ml of water, adjusting the alkalinity to 0.2g / L, and boiling at 80℃ for 1 hour. Finely break down the material at a concentration of 3% using a Walley pulper for 150 minutes, achieving a fineness of 154 ml.
[0065] The resulting nitrocellulose (exploding cotton) has a nitrogen content of 193.7 ml / g, a 3% acetone viscosity of 7501 mpa.s, a fine fiber content of 68.1%, and meets the requirements for alcohol-ether solubility, fineness, and stability. It can be used in the production of gelatinous explosives for underwater blasting.
[0066] Dissolution test: In DEP solvent, the viscosity of the 1.2% (moisture content) popping cotton solution reached 600 mPa·s after 10 minutes and 1800 mPa·s after 60 minutes.
[0067] Gel test: In nitroglycerin and triacetyl ester, 3.1% (dry weight) of the blister pack gelled in a beaker for 10 minutes and then inverted, maintained stable gel for 4 minutes without falling off.
[0068] Comparative Example 2
[0069] Add 2000g of a nitric acid-sulfur mixture to a 3000ml beaker equipped with a mechanical stirrer. Maintain the temperature at 18℃ for 10 minutes, then start stirring. The mass fractions of the components in the mixture are 27.26% nitric acid, 56.79% sulfuric acid, and 15.95% water. Weigh 50g of M1000 refined cotton dried to below 10% moisture content. Sift the cotton powder through a 5-mesh sieve for 10 minutes, then add the sieved refined cotton to the mixture. After 40 minutes, filter the mixture and nitrocellulose. Wash the nitrocellulose until it reaches a weakly acidic / neutral pH. Acid-wash the washed nitrocellulose in a beaker containing 2000ml of water, adjusting the acidity to 2g / L. Acid-wash at 80℃ for 2 hours. After acid cooking, wash until weakly acidic / neutral. Then, perform an alkaline wash in a beaker containing 2000ml of water, adjusting the alkalinity to 0.2g / L. Cook at 80℃ for 1 hour. Finely break down the nitrocellulose using a Walley pulper at a 3% material concentration for 150 minutes, achieving a fineness of 157ml. Next, sieve using a 40-mesh standard sieve, collecting the residue as the product. Place the product in 2000ml of water, stir at 1000r / s for 10 minutes, allow to settle naturally for 15 minutes, discard the supernatant, filter the material through a cloth bag, and dehydrate to obtain the bursting cotton product.
[0070] The resulting nitrocellulose (exploding cotton) has a nitrogen content of 193.2 ml / g, a 3% acetone viscosity of 7300 mpa.s, a fine fiber content of 52.3%, and meets the requirements for alcohol-ether solubility, fineness, and stability. It can be used in the production of gelatinous explosives for underwater blasting.
[0071] Dissolution test: In DEP solvent, the viscosity of the 1.2% (moisture content) popping cotton solution reached 3000 mPa·s after 10 minutes and 4500 mPa·s after 60 minutes.
[0072] Gel test: In nitroglycerin and triacetyl ester, 3.1% (dry weight) of the blister cotton gelled in a beaker for 10 minutes and then inverted, maintained stable gel for 70 minutes without falling off.
[0073] Comparative Example 3
[0074] Add 2000g of a nitric acid-sulfur mixture to a 3000ml beaker equipped with a mechanical stirrer. Maintain the temperature at 18℃ for 10 minutes, then start stirring. The mass fractions of the components in the mixture are 27.26% nitric acid, 56.79% sulfuric acid, and 15.95% water. Weigh 50g of M1000 refined cotton dried to below 10% moisture content, loosen it, and add it to the mixture. After 40 minutes, filter the mixture and the nitric acid-cotton mixture. Wash the nitric acid-cotton mixture until it is weakly acidic / neutral. Acid-wash the washed nitric acid-cotton mixture in a beaker containing 2000ml of water, adjusting the acidity to 6g / L, and boiling at 70℃ for 3 hours. After acid boiling, wash until it is weakly acidic / neutral. Alkali-wash the washed nitric acid-cotton mixture in a beaker containing 2000ml of water, adjusting the alkalinity to 1.5g / L, and boiling at 90℃ for 1.5 hours. Finely break down the material at a concentration of 3% using a Walley pulper for 80 minutes, achieving a fineness of 149 ml.
[0075] The resulting nitrocellulose (exploding cotton) has a nitrogen content of 193.9 ml / g, a 3% acetone viscosity of 6900 mpa.s, a fine fiber content of 56.7%, and meets the requirements for alcohol-ether solubility, fineness, and stability. It can be used in the production of gelatinous explosives for underwater blasting.
[0076] Dissolution test: In DEP solvent, the viscosity of the 1.2% (moisture content) popping cotton solution reached 1100 mpa.s after 10 minutes and 2600 mpa.s after 60 minutes.
[0077] Gel test: In nitroglycerin and triacetyl ester, 3.1% (dry weight) of the blister pack gelled in a beaker for 10 minutes and then inverted, maintained stable gel for 40 minutes without falling off.
[0078] As can be seen from the above examples, the embodiments of this application are improvements on the process and process parameters of the comparative examples. In Comparative Example 1, there were no improvements to the raw material screening and fine-cutting water screening, sedimentation process, or acid washing and alkali washing process parameters; in Comparative Example 2, there were no improvements to the acid washing and alkali washing process parameters; in Comparative Example 3, compared to Comparative Example 1, only the boiling and fine-cutting processes were optimized. Therefore, compared with the comparative examples, the embodiments have fewer fine fibers, resulting in excellent solubility and gelling properties.
[0079] Based on the test results of the above embodiments and comparative examples, it can be seen that the extruded cotton product prepared in this application is easier to break into finer pieces. After boiling and washing, the extruded cotton can be broken into pieces with a fineness of 150 ml in just 80 minutes. It dissolves faster in solvents such as DEP; 1.2% moisture content extruded cotton can be completely dissolved in just 1 hour. It gels faster and produces more stable gels in triacetin and nitroglycerin. 3.1% dry weight extruded cotton forms a gel in a beaker for 10 minutes, and after being inverted, the gel remains stable for more than 60 minutes without falling off. Therefore, the extruded cotton obtained in this application has better solubility and gelling properties, making it better suited for the production of gelatinous explosives for underwater blasting.
[0080] Obviously, those skilled in the art can make various modifications and variations to this invention without departing from its spirit and scope. Therefore, if these modifications and variations fall within the scope of the claims of this invention and their equivalents, this invention also intends to include these modifications and variations.
Claims
1. A method for preparing high-quality bursting cotton, characterized in that, Includes the following steps: S1. Sift the refined cotton through a sieve to remove cotton dust; S2. Refined cotton undergoes a nitration reaction in a mixed acid of nitrate and sulfur, followed by filtration and rinsing with tap water to obtain nitrocellulose. S3. The nitrocellulose is subjected to acid boiling, water washing, alkali boiling, and fine cutting. S4. The material obtained in S3 is subjected to a water sieve; S5. The material obtained in S4 is subjected to a sedimentation process to remove fine fibers by stirring, settling, and taking water. In step S3, the acid used for acid boiling is calculated as sulfuric acid, with a zero acidity of 5~7 g / L, the acid boiling temperature is 50~80℃, and the acid boiling time is 2~5 h; the alkalinity used for alkali boiling is calculated as sodium carbonate, with a zero alkalinity of 0.5~3.0 g / L, the alkali boiling temperature is 80~110℃, and the alkali boiling time is 1~4 h. In step S5, the stirring, settling, and water extraction methods include: first stirring evenly, then performing settling treatment, controlling the settling time, and extracting the upper layer water and the fine fibers contained in the upper layer water.
2. The method for preparing high-quality bursting cotton according to claim 1, characterized in that, In step S1, the screen mesh size is 5-20 mesh, the sieving time is more than 10 minutes, and the sieving process disperses the clumps of material; the refined cotton has a moisture content of 5-10% and a degree of polymerization of more than 2000.
3. The method for preparing high-quality bursting cotton according to claim 1, characterized in that, In step S2, the weight percentage of the nitric acid-sulfur mixture includes: 26.00%–35.00% nitric acid, 45%–61% sulfuric acid, and 13.00%–20.00% water; the nitration reaction time is 30–60 min.
4. The method for preparing high-quality bursting cotton according to claim 1, characterized in that, In step S3, the fineness of the fine-fractionation process is 100~180ml, and the fine-fractionation time is 50~150min.
5. The method for preparing high-quality bursting cotton according to claim 1, characterized in that, In step S4, the mesh size of the water sieve is 40-120 mesh, and the material is rinsed with tap water during the water sieve process.
6. The method for preparing high-quality bursting cotton according to claim 1, characterized in that, The stirring time is more than 10 minutes, and the stirring speed is 500~3000 r / min; the settling time is 10~30 minutes.
7. A high-quality bursting cotton, characterized in that, It is prepared by the preparation method described in any one of claims 1-6.
8. The high-quality bursting cotton according to claim 7, characterized in that, The high-quality extruded cotton is used in the production of gelatinous explosives for underwater blasting.
Citation Information
Patent Citations
Method for preparing superhigh-viscosity energy-containing cellulose nitrate
CN102219862A
Manufacture of cellulose nitrate
CA448694A
Environment-friendly gunpowder for replacing single-base powder and double-base powder in fireworks
CN111592437A